Competitive Improvement Strategies of The Coconut Oil Industry at PT XYZ - Muhammad Aulia Ramadhan; Yudha Heryawan Asnawi; Siti Jahroh (Publikasi Indonesia, 2024)
This study aims to develop strategies for enhancing competitiveness in the coconut oil industry amidst intense competition. It analyzes the internal and external conditions of PT XYZ, focusing on optimizing strengths and opportunities while leveraging an Initial Public Offering (IPO) strategy. The study examines the internal and external conditions of PT XYZ to develop strategies for improving competitiveness. Utilizing qualitative methods, the research employs analytical tools such as the Internal Factor Evaluation (IFE) and External Factor Evaluation (EFE) matrices, SWOT analysis, and the Quantitative Strategic Planning Matrix (QSPM). The sample consists of 15 respondents, including 11 internal and 4 external participants. Results show that the company’s internal conditions, with 5 strengths and 4 weaknesses, yield an IFE score of 3.03. In contrast, the external conditions, featuring 5 opportunities and 4 threats, result in an EFE score of 2.92. This analysis places PT XYZ in Quadrant IV of the IE matrix, indicating a